2001
DOI: 10.1093/bmb/60.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The thrifty phenotype hypothesis

Abstract: The thrifty phenotype hypothesis proposes that the epidemiological associations between poor fetal and infant growth and the subsequent development of type 2 diabetes and the metabolic syndrome result from the effects of poor nutrition in early life, which produces permanent changes in glucose-insulin metabolism. These changes include reduced capacity for insulin secretion and insulin resistance which, combined with effects of obesity, ageing and physical inactivity, are the most important factors in determini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
1,589
6
72

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 2,345 publications
(1,712 citation statements)
references
References 45 publications
45
1,589
6
72
Order By: Relevance
“…From the point of view of cardiovascular risk, epidemiological studies have demonstrated an association between chronic and degenerative diseases such as diabetes,3, 4 CVDs, and environmental (epigenetic) conditions in the embryonic or foetal phase 5, 6, 7. From the epidemiological studies conducted in England and Wales by Barker et al , The Foetal Programming Hypothesis or ‘Baker's Hypothesis’, finally, important review addressed the various environmental, hereditary, and genetic factors involving the interaction between the parents, placenta, and embryo in the genesis of diseases of adult life, citing epigenetic factors such as nutritional deficiencies and vitamins 8…”
Section: Introductionmentioning
confidence: 99%
“…From the point of view of cardiovascular risk, epidemiological studies have demonstrated an association between chronic and degenerative diseases such as diabetes,3, 4 CVDs, and environmental (epigenetic) conditions in the embryonic or foetal phase 5, 6, 7. From the epidemiological studies conducted in England and Wales by Barker et al , The Foetal Programming Hypothesis or ‘Baker's Hypothesis’, finally, important review addressed the various environmental, hereditary, and genetic factors involving the interaction between the parents, placenta, and embryo in the genesis of diseases of adult life, citing epigenetic factors such as nutritional deficiencies and vitamins 8…”
Section: Introductionmentioning
confidence: 99%
“…This process is highly susceptible to changes in the intrauterine environment. Epidemiological studies have suggested an association between poor fetal or infant growth and increased risk of developing glucose intolerance and metabolic syndrome later in life [1,2]. A recent review study suggested that inadequate maternal nutrition might disturb the development of the fetus, which must adopt strategies to ensure survival that will programme its future health [3].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance (31) and IHD (32) have been associated with low insulin-like growth factor 1 concentrations in observational studies. For the purposes of the present review (10) .) (26) Body composition: Rivera et al (27) Blood pressure: Webb et al (29) Glucose: Conlisk et al (28) Ben-Schlomo et al (30) Blood pressure: Hawkesworth et al (34) Body composition: Hawkesworth et al (35) Date Rivera et al (27) : 1988-9; (subjects exposed during pregnancy until 3 years of age) Webb et al (29) and Conlisk et al (28) 1997-8 (subjects exposed during pregnancy until 7 years of age)…”
Section: Protein-energymentioning
confidence: 98%
“…Evidence that CVD risk may be related to early-life, specifically intrauterine, exposures was initially derived from the inverse association between birth weight and CVD mortality (3)(4)(5) and/or risk factors such as blood pressure (6,7) insulin resistance (8) and the metabolic syndrome (9) . One of the most-widely-cited hypotheses, termed the 'thrifty phenotype' (10) , suggests that when exposed to deprived conditions during development fetal adaptations (metabolic, endocrine and/or anatomical) occur that allow for immediate survival but may be maladapted to cope with the demands of a more-affluent lifestyle in later life (Fig. 1).…”
Section: Developmental Origins Of Health and Disease: Maternal Supplementioning
confidence: 99%